IMPLEMENTATION OF HR-ENGINEERING AS AN INNOVATIVE VECTOR OF THE DEVELOPMENT OF THE BUSINESS ECONOMY OF THE ORGANIZATION IN THE CONDITIONS OF GLOBALIZATION AND EUROPEAN INTEGRATION (Development Service Industry Management, 2024)
The composition  of business processes that are appropriate to implement the system of HR-engineering in a modern enterprise. The main tasks, principles and stages of HR-engineering implementation at the enterprise are  considered. Detailed description of the complex of works in the practical application of the principles of  engineering business process in the enterprise. The positive and negative consequences of the introduction  of the method of engineering business processes.HR-engineering is implemented at all levels of business  process management and isdeveloped in different ways of changing the business  environment.  HR-engineering  techniques  include  the  latest tools,  advanced  technologies and tools for the transformation of HR-processes and their optimization using digitalization. The  study  systematizes  the  latest  technologies  and  tools  of  HR  management  and  describes  their integrated application in HR-engineering technology. A conceptual scheme for understanding HRprocesses  as  an  important  component  of  business  processes  of  the  enterprise  is  proposed.The article examines the use of modern HR technologies in enterprise management. Social challenges and modern business priorities regarding the transformation of HR processes have been studied. The global trends of the innovative development vector of digitalization of HR of the organization have been determined. The essence of the reengineering process was formed as a direction of improving business processes in the organization's HR engineering system. The stages of the introduction of HR engineering as an innovative vector of the development of the organization's business economy have been constructed. The map of the restructuring of the business process "forming the personnel potential of the enterprise" on the basis of reengineering is substantiated. The main means of HR engineering, which are used during the design and optimization of HR processes, are given. The positive consequences of the practical application of the HR-engineering method of business processes at the enterprise are characterized.
Keywords: business process; engineering; reengineering; hr-technology; personnel management; building an HR-engineering system